Clone hop domination number of a graph. (4th July 2019) - Mahadevan, G.; Vijayalakshmi, V.
Abstract: In this paper we introduce the concept of clone hop domination number of a graph. A set S ⊆ V is a hop dominating set of G, if for every vertex u ∈ V – S, there exists u ∈ S such that d ( u, v ) = 2. A set S ⊆ V is a clone hop dominating set of G, if S is a hop dominating set and has a perfect matching. The minimum cardinality of clone hop dominating set is called clone hop domination number of G and it is denoted by CHD(G). In this paper we initiate this paramter and discuss various interesting results.